A perspectiva da educação diante as tecnologias digitais no cenário escolar. - Sousa, Rodrigo Oliveira de (Universidade Federal do Tocantins, 2021)
This work aims to present possible strategies for teachers in the early years of elementary school to work with digital technologies in their pedagogical practices in the school environment. There is also a dialogue about how technologies over time have been developed and thought out in the school context. The research methodology was based on a bibliographic search to try to understand the importance and what is discussed about digital technologies in basic education, articulating with authors about the importance of digital media, especially those that are on the internet, causing strategies and possibilities for appropriate these digital resources together with students. As strategies and possibilities for the development of the appropriation of digital technologies, the relevance of teacher training is perceived as a prerequisite or fundamental principle for working with digital technologies, this would be a necessary condition to achieve the expected objectives and also satisfactory for their students. In addition, the teacher's role in actively working with digital technologies is presented, as it is not enough just to have them available, but they must use them in a way that provides a better use in order to reach their goal. Therefore, the results of the research demonstrate some strategies, such as the use of the internet, social media, games and other digital resources, to be incorporated into the context of students and academic training.